Nuevos aportes a la genética del hipotiroidismo congénito y de la resistencia a hormonas tiroideas : identificación y caracterización molecular de las mutaciones responsables - Osorio Larroche, Carolina (2014)
The thyroid gland is the first endocrine gland to appear in embryonic development. About week 11 of gestation, fetal thyroid gland and has the ability to concentrate iodide and approximately 18 weeks, begins to release thyroid hormones. The contribution of endogenous hormones is essential for brain maturation and the fetal skeleton. Deficiency of thyroid hormones, even for short periods may lead to irreversible brain damage whose consequences depend on the time of onset and duration of the deficiency. The prevalence of neonatal hypothyroidism is 1/3000-1/4000 from neonatal screening programs. In hypothyroidism several entities have their own characteristics, congenital hypothyroidism without goitre (dysembriogenesis) due to agenesis, ectopia or hypoplasia, corresponding to 80-85% of cases of neonatal hypothyroidism. Some cases where the cause is a mutation in TTF-1, TTF-2 , Pax 8, NKH2-5 and TSH receptor genes were identified. A second group is made up of neonatal hypothyroidism Congenital hypothyroidism with goitre or goiter due to congenital abnormalities of some of the components of the biosynthesis of thyroid hormones (dyshormonogenesis): thyroid peroxidase (TPO), thyroglobulin (TG), DUOX2, NIS, pendrin and dehalogenase I. This group corresponds to the 15-20% of neonatal hypothyroidism and is characterized by low levels of thyroid hormones and consequently greater increase TSH and thyroid cell proliferation. Goitre usually occurs when the thyroid gland is unable to produce enough thyroid hormone to meet the demands of the individual. The thyroid gland enlarges to compensate for this situation, which usually overcomes mild deficiencies of thyroid hormone is correct but not severe.\nThe biosynthesis of thyroid hormones is performed in cell-colloid interface in the apical membrane of the thyroid cell, on a structural glycoprotein of large size is TG. This is more efficient protein formation of thyroid hormones in the presence of physiological concentrations of iodide. In addition to intervening in the biosynthesis of thyroid hormones also serves for the storage of iodide. Iodide enters active thyroid gland and must be oxidized before acting as an effective agent iodination. Enter the cell cytoplasm through the NIS transporter located in the basolateral membrane of the thyrocyte. A second conveyor located at the apical membrane, the pendrin leads to the interface iodide cell / colloid. The three stages of iodide organification: oxidation implement into the tirosilic residues of thyroglobulin and finally coupling the monoyodotirosinas and diyodotirosinas to form the thyroid hormones triiodothyronine (T3) and tetraiodothyronine (T4) are catalyzed by the same enzyme microsomal membrane, TPO and in the presence of a source of H202. Two enzymes are related to the synthesis of H2O2, these two NADPH oxidases bound to the apical membrane called DUOX1 and DUOX2, and two maturation factors and DuoxA DuoxA1. The biosynthesis of thyroid hormones is regulated by TSH who exerts its stimulatory action of thyroid transcription of specific genes by interacting with its receptor. The effect of thyroid hormones is exerted at the transcriptional level through their interaction with the nuclear receptor. Dispersed throughout TPO gene mutations are the most common cause of congenital hypothyroidism dyshormonogenesis permanent. The gene encoding human TPO, exons 17 is located on chromosome 2 in the range 2p24-p25. Amino acids 149 to 711 corresponding to exons 5 to 12 in the human TPO gene show significant similarity to the consensus called "animal haem peroxidase" (An peroxidase). Exons 13 and 14 have homology to the family of genes called "Control complement protein (CCP) -like" (residues 742-795) and "calcium-binding epidermal growth factor (EGF) -like" (residues 796-839), respectively. Exon 15 encodes the transmembrane domain and exons 16 and 17 for the intracytoplasmic region.\nKnowledge of the structural organization of the gene for human TPO allowed to develop the skills to identify mutations that cause congenital goiters that protein deficiency tools. These studies enabled the design primers to PCR amplify intron each of the 17 exons of thyroid peroxidase and consequently study, from the genomic DNA of patients with iodide organification default caused by TPO gene mutations. So far, more than 80 mutations have been described in the TPO gene which is inherited in an autosomal recessive manner. In about 20% of cases of permanent congenital hypothyroidism, monoallelic defects have been identified in this gene, presumably because of mutations not found in cryptic intron or regulatory regions of the gene. Thus, it has been reported only monoallelic expression of the mutant allele. The present need to analyze how these different mutations located in different domains of TPO gene alter the functionality of the respective protein and cause congenital goiter. This will allow a breakthrough in the understanding of the pathophysiology of the disease and clinical correlation with phenotypic variability.\nA second entity is resistance to Thyroid Hormone (RTH), characterized by a decreased\nresponse to T3 by tissue. RTH incidence is 1 in every 50,000 live births, with over 600\nknown cases. There are two genes encoding a thyroid hormone receptor, the THRalfa gene is located on chromosome 17 and gene THRbeta of 10 exons on chromosome 3. 90% of the mutations are located in the LBD domain (Ligand Binding Domain ) of THRbeta gene and are inherited in an autosomal dominant manner. Have been described about 200 mutations within those which predominate amino acid change. Only two mutations have been recently described in THRalfa gene. Regarding polymorphisms in the gene, is not known yet about the role much the same. Recent studies have shown the association of these with TSH levels, this is the case of polymorphism THR?-in9-G / A which explains an increased concentration of TSH allele manner dose dependent. \nIn relation with congenital hypothyroidism one of our objectives was identify mutations in the TPO gene because this mutations are present in the greatest frequence. Five patients with congenital hypothyroidism with goiter by defects in organification of iodine were analyzed. RFLP PCR-test was used to check the presence or absence of mutation p.R396fsX472 generated by insertion-duplication homozygous GGCC position 1277 in the eighth exon of TPO gene that generates a change in the reading frame resulting in a premature exon 9, with the production of a truncated protein with no biological activity codon. Then, PCR-sequencing technique of the promoter and 17 exons of TPO gene was carried out after of the pre-tuning the better conditions for amplification of each exon. A reported mutation was identified, p.E799K and two rare variants of sequence: P. V748M and c.2007-11_2007-9del (-CTT). Cloned system pGEM-T Easy Vector for the characterization of the heterozygous deletion identified. The allelic segregation was studied in the familial groups of our patients. Also, reported and new polymorphisms were identified in the five patients.\nWith respect of RTH, 11 patients with suspected this patology were studied. In order to\nidentify new mutations we amplified by PCR and sequenced exons 7,8,9 and 10 of THRbeta gene using intronic primers. Two mutations described above p. A268G, p.G345R were identified and a de novo mutation p.P452L. The last mutation was confirmed by poblational studies to discard the presence of a polymorphism. \nThe identified alterations were analyzed with different bioinformatics tools. Protein homology analysis, prediction of protein secondary structure prediction of the functional impact of amino acid substitutions which are identified and the effect of possible consensus mutations found in regions cause splicing was performed on this process. Silico studies 3D were carried. We have to mention the importance of the homology modeling to this study.\nThe molecular biology techniques used here, are an important tool to the understanding of the molecular physiopathology of the neonatal hypothyroidism and RTH. They will contribute to the early diagnostic and the selection of the appropriate treatment enabling too, the adequate genetic counseling to affected families.